An introduction to the discipline of Fiqh al-mu'amalat and economics - Muji Tahir , Hailani; Laluddin, Hayatullah (2009)
The aim of this paper is to provide a basic understanding of the disciplines of Mu'amalat and Economics from theoretical and practical aspects in contemporary transactions. The invention of new products in the current practice is not as easy as it might be assumed, for it requires a high level of expertise. This is to make sure that these products are in line with contemporary needs and are compatible with Shari'ah rulings. Failure in this regard will jeopardize the credibility of the financial system which is based on Islam. The weakness and loopholes in management and administration due to the attitude of leadership will lead to negative perception of Islamic financial system. The success of the system is dependent on an integrated and holistic understanding rather than partial one. Clarity of vision and understanding will help those involved in the system to improve their capacity and self confidence, finally enhancing the reputation of Islamic financial institutions. This present a huge Challenge for fuqaha and economists, in establishing the system, hence, require cooperation and full commitment and strong conviction.